Prevalence and correlates of postsecondary residential status among young adults with an autism spectrum disorder. (July 2014) - Anderson, Kristy A; Shattuck, Paul T; Cooper, Benjamin P; Roux, Anne M; Wagner, Mary
This study examined the prevalence and correlates of three living arrangements (with a parent or guardian, independently or with a roommate, or in a supervised setting) among a nationally representative sample of postsecondary young adults with an autism spectrum disorder. We assessed living arrangements since leaving high school. Compared with young adults with other disability types (learning disabilities, intellectual disabilities, or emotional disturbances), those with an autism spectrum disorder were more likely to have lived with a parent or guardian and least likely ever to have lived independently since leaving high school. Members of the autism spectrum disorder group were less likely to have ever lived elsewhere and more likely to live under supervision since leaving high school compared to persons with emotional disturbances and learning disabilities. Group differences persisted after controlling for functional ability and demographic characteristics. Correlates of residential independence included being White, having better conversation ability and functional skills, and having a higher household income. Further research is needed to investigate how these residential trends relate to the quality of life among families and young adults.